A Study of optimum oil palm frond (OPF) ratio in cement sand brick - Khairunnisa, Muhammad Husain (2016)
This paper is an overview to investigate the properties of oil palm frond (OPF) fiber content in cement sand bricks. The objective of this thesis is to determine the optimum ratio of the OPF in the production of cement sand brick. This thesis also wants to determine the characteristic of the cement sand brick with OPF fiber content in term of compressive strength, density and water absorption. From the results, it shows that the mix proportion 1:5:1 (OPF1.0) was the optimum ratio of OPF fiber content because it give the highest compressive strength which is 8.000 Mpa at 28 days. The results indicate that the compressive strength of cement sand bricks with OPF fiber content is decreased as the OPF fiber content increased in the mix ratio. In addition, the mix proportion 1:5:1 (OPF1.0) gives the highest density result which is 1658.08 kg/m3 and the lowest water absorption result which is 9.83%. Generally, the properties of OPF cement sand brick are slightly lower that plain cement sand brick (OPF0). The density of cement sand bricks with OPF fiber content was decreased with the increasing additional of OPF fiber content and it is decreasing linearly with the increasing of OPF fiber content. The percentage of water absorption also found to be increased linearly with the increasing of OPF fiber content. Besides that, it is also found that additional of excessive OPF fiber content in the production of cement sand brick was decrease the compressive strength and continues to increase the water absorption hence decrease the density. It can be concluded that the usage of OPF has a great potential in the production of cement sand brick and also in the construction industry. It is also may help to maximize the usage of OPF and can minimize the OPF to be thrown away in landfills